Multi-needs for multi-screening: practices, motivations, and attention distribution - Dias, Patrícia (2021)
Multi-screening is an emergent but fast-growing and fast-changing practice, evolving along with the technologies that mediate it. This article presents a study on multi-screening, i.e., simultaneously or sequentially engaging with more than one screened-media. Based on the uses and gratifications theory, our study focused on the most common multi-screening scenario—engaging with the smartphone while watching TV—in order to explore triggers, motivations, gratifications, and attention distribution. The methodology is qualitative in nature, including ethnographic journals and follow-up interviews to a sample of 30 young adults, and the data was collected in Portugal and Spain. The activities performed on each device are usually disconnected and motivated by the need to enhance the entertainment afforded by the TV or to obtain a sense of efficiency. The attention is distributed in alternated periods, and the smartphone has a greater ability of demanding attention and retaining the engagement.